2021
DOI: 10.3390/ijms222011247
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways in Prolactinomas: Translational and Therapeutic Implications

Abstract: Prolactinoma has the highest incidence rate among patients with functional pituitary tumours. Although mostly benign, there is a subgroup that can be aggressive. Some clinical, radiological and pathology features have been associated with a poor prognostic. Therefore, it can be considered as a group of heterogeneous tumours. The aim of this paper is to give an overview of the molecular pathways involved in the behaviour of prolactinoma in order to improve our approach and gain deeper insight into the better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…Prolactin, dopamine and other factors control lactotroph homeostasis ( 7 , 19 , 48 , 52 , 65 ). For patients where dopamine agonists are inefficient, it is worth consideringwhether the pathogenesis of those tumors is the same as in those responsive to dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolactin, dopamine and other factors control lactotroph homeostasis ( 7 , 19 , 48 , 52 , 65 ). For patients where dopamine agonists are inefficient, it is worth consideringwhether the pathogenesis of those tumors is the same as in those responsive to dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…If such factors can be identified, the exploration, for example, of PRLR or PRLR-associated pathways, not only in terms of mutations but also in gene expression regulation or modulatory molecules using high throughput technologies in patients, could help in designing a specific personalized therapy ( 63 , 65 , 67 , 68 ),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five different dopamine receptors can be dived into two categories depending on the action of the G protein. 53,54 When dopamine binds to the D2 receptor, it leads to the expression of certain genes and the reduction of prolactin exocytosis. [55][56][57][58][59] As with these findings, in previous studies, subacute exposure to styrene led to dopamine depletion in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In healthy individuals, binding of dopamine to D2 receptors inhibits the release of secretory granules containing prolactin within seconds, but it takes persistent dopamine action and days before inhibition of lactotroph proliferation. 34 The notoriously short half-life of L-Dopa, even if administered together with a DCI, is responsible for the fluctuation of symptoms in patients with Parkinson's disease and inherited neurotransmitter disorders treated with L-Dopa/DCI, and may necessitate 3-6 daily doses. 15 A single case study from 1998 clearly demonstrated that even with 6-time dosing of L-Dopa during daytime, prolactin concentrations remain high during the night, but the peaks are markedly ameliorated just by switching to 3-time dosing of a slow-release formulation.…”
Section: Treatment and Clinical Follow-upmentioning
confidence: 99%